Assessing larval connectivity for marine spatial planning in the Adriatic. (April 2017) - Bray, L.; Kassis, D.; Hall-Spencer, J.M.
Abstract: There are plans to start building offshore marine renewable energy devices throughout the Mediterranean and the Adriatic has been identified as a key location for wind farm developments. The development of offshore wind farms in the area would provide hard substrata for the settlement of sessile benthos. Since the seafloor of the Adriatic is predominantly sedimentary this may alter the larval connectivity of benthic populations in the region. Here, we simulated the release of larvae from benthic populations along the coasts of the Adriatic Sea using coupled bio-physical models and investigated the effect of pelagic larval duration on dispersal. Our model simulations show that currents typically carry particles from east to west across the Adriatic, whereas particles released along western coasts tend to remain there with the Puglia coast of Italy acting as a sink for larvae from benthic populations. We identify areas of high connectivity, as well as areas that are much more isolated, and discuss how these results can be used to inform marine spatial planning and the licensing of offshore marine renewable energy developments. Highlights: Dispersal of macroinvertebrate larvae from the Adriatic Sea coastline is simulated. The effect of pelagic larval duration on dispersal is investigated. Model outputs indicate currents typically carry larvae westwards. Puglia coast of Italy appears to act as a sink for larvae from benthic populations.